Risk assessment of SARS‐CoV‐2 infection in free‐ranging wild animals in Belgium. Issue 3 (26th May 2021) - Logeot, Myriam; Mauroy, Axel; Thiry, Etienne; De Regge, Nick; Vervaeke, Muriel; Beck, Olivier; De Waele, Valérie; Van den Berg, Thierry
Abstract: The aim of this review paper is to evaluate the putative susceptibilities of different free‐ranging wild animal species in Belgium to SARS‐CoV‐2 and provide a risk assessment of SARS‐CoV‐2 infection in those animals. Since the onset of the COVID‐19 pandemic, natural SARS‐CoV‐2 infections have mainly been confirmed in domestic and production animals, and in wild animals kept in captivity, although the numbers remain limited when compared to human cases. Recently, the first SARS‐CoV‐2 infections in presumably escaped minks found in the wild have been detected, further addressing the much‐feared scenario of transmission of the virus to animals living in the wild and its consequences. Considering the most likely origin of the virus being a wild animal and the putative susceptibilities of free‐ranging wild animal species to SARS‐CoV‐2, the risk of infection with possible establishment of the virus in these populations has to be investigated closely. The authors conclude that most attention should be given to surveillance and awareness‐raising activities for SARS‐CoV‐2 infection in wild mustelids, bats, wild canids and felids, particularly these collected in wildlife rescue centres. People involved in frequent and close contact with wild animals should take all necessary precautionary measures to protect wild animals against exposure to the virus. More than one year after the first detection of SARS‐CoV‐2 in humans, the time has come to increase investments in research and surveillance activities in animals, including in free‐ranging wild animals, as part of a One Health control of this pandemic. This study focussing on Belgium could be helpful for other countries with similar animal densities and ecosystems.